BAHASA PERSUASIF PADA IKLAN KOSMETIK DI TELEVISI - Agustin, Riky Juwita Putri; Kasnadi; Astuti, Cutiana Windri (Jurnal Bahasa dan Sastra, 2021)
Persuasive language is a sentence that aims to invite and influence someone to follow what they want. The purpose of this study was to explain the use of persuasive language through rationalization, suggestion and conformity technique within cosmetic advertisements on television. The research is designed as descriptive qualitative, specifically discourse analysis. To analyze data, the researcher classified the types of persuasive language based on the Keraf ’s classification (2007), including rationalization, suggestion, and conformity techniques. A total of 51 cosmetics advertisement were chosen. The result of study showed that a number of techniques were clearly used in cosmetics advertisements in TV. Firstly, rationalization technique used in 17 cosmetic advertisements marked by the number of products, benefits, ingredients, and result obtained after using these cosmetic products. Secondly, suggestion technique used in 22 cosmetic advertisements, marked by showing the advantages of using the cosmetic products. Lastly, conformity technique used in 12 cosmetic advertisements which marked by the use of national artists or public figures.